Analysis of Cadmium Content in The Soil Using SilverÂ Mercury Amalgam Electrode with Stripping Differential Pulse Anodic Voltammetry Technique - Asilah, Asri
Cadmium is one of the heavy metal sources of envirorunental pollutant. The exposure of cadmium at certain amount and certai n tim e period can cause health issues for human, suc h as cancer, kidney disease, digestive disorder, reproductive system disease, etc. In this research, a method was developed to determine cadmium using voltammehy method. The working electrode used was silver-mercuty amalgam. The deposition process of amalgam forming on silver wire was canied out at -400 m V for 600 seconds. Cadmium measurement was carried out using stripping differential pulse voltammet.y technique with -1100 mV of deposition potential and 180 seconds of deposition time. The amalgam working-electrode has a good repeatability and the linear regions of 1 - 10 ppb, 20 - 100 ppb, and 200 - 1000 ppb can detect cadmium up to 1.05 ppb. The result of cadmium content in the soil using Stripping DPV was 65,29 ± 1,29 mg/kg with 97,82% recovery. The performance test of the analytical method was caiTied out by comparing the result with the measurement result using AAS method. The result of the petformance test of the analysis method using t-test shows that both of these results from tv.ro different methods do not have any significant difference at 95% confidence level.